2018
DOI: 10.1051/shsconf/20184003010
|View full text |Cite
|
Sign up to set email alerts
|

Parenting in low-income families from the perspective of social work

Abstract: Abstract. The family is the primary socializing factor. Its mission is to create a stable and safe environment for the child and for his comprehensive development. The role of parents is to give to a child the values and norms accepted in the society, which is a prerequisite for successful integration of a child into society. That is why the upbringing function of the family is regarded as one of the main. This feature is, however, influenced by many factors. The goal of the study was to find how poverty affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Students with high-income parents were 31% less likely to lose school hours due to acute dental care than students with low-income parents. Further, students from low-income families consider that the priority is to purchase food and clothing (Banovcinova, Mydlikova, & Vodicková, 2018). The result from this study is in line with past studies analyzing economic valuation for dental health, stating that monthly income is a determining factor that influences WTP positively (Mubaraki et al, 2017;Srivastava et al, 2019;Walshaw et al, 2019).…”
Section: Figure 2 Willingness To Pay For Caries Preventionsupporting
confidence: 87%
“…Students with high-income parents were 31% less likely to lose school hours due to acute dental care than students with low-income parents. Further, students from low-income families consider that the priority is to purchase food and clothing (Banovcinova, Mydlikova, & Vodicková, 2018). The result from this study is in line with past studies analyzing economic valuation for dental health, stating that monthly income is a determining factor that influences WTP positively (Mubaraki et al, 2017;Srivastava et al, 2019;Walshaw et al, 2019).…”
Section: Figure 2 Willingness To Pay For Caries Preventionsupporting
confidence: 87%
“…Furthermore, it has an indirect influence on parents’ beliefs in terms of focusing on survival and meeting the basic needs of providing food for the family more than ensuring that children have adequate opportunities to achieve development outcomes [ 42 , 53 ]. In dire situations which have led to families living in poverty, poverty affects the entire family functioning, including parenting and its various dimensions (such as supervision, monitoring and consistency in the use of such discipline) [ 56 , 57 ]. Less affluent are less likely to afford quality child care which may have an indirect impact on child safety and their children may receive lower-quality of care [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical evidence suggests that the socio‐economic context of families may influence parenting practices (Bøe et al, 2014; Callahan & Eyberg, 2010; Doepke & Zilibotti, 2019; Roubinov & Boyce, 2017). Banovcinova et al (2018) investigated how poverty affected parenting using the Alabama Parenting Questionnaire (APQ) in a Slovakian sample consisting of 188 respondents living below the poverty line. Their results indicated differences between parents living in poverty and parents with a standard rate of income, especially in monitoring and supervision, and in the use of positive disciplinary techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These factors indicate or are associated with lower levels of SES and physical and psychological stressors (Clifford et al, 2015). Nevertheless, few studies have investigated parenting practices in a child welfare context (Banovcinova et al, 2018; Kohl et al, 2011). In a study on families involved in child welfare services, Rodriguez‐JenKins and Marcenko (2014) found that parenting stress differs according to placement status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation